LPSE Biro Pengadaan Barang dan Jasa Provinsi Jawa Timur Peran Frontdesk dalam Mencapai Kepuasan Penyedia pada sistem - Khumairoh, Lutfiatu; Reviandani, Oktarizka (LPPM STISIP IMAM BONJOL, 2025)
Frontdesk is an innovation created by the East Java Provincial Goods and Services Procurement Bureau, LPSE section, with a Helpdesk system that places several employees at the front (Frontliners) as recipients of providers to fulfill providers' requests and complaints regarding the public procurement process. Good public services are public services that focus on provider satisfaction through optimizing employees of the East Java Provincial Goods and Services Procurement Bureau in creating good communication with providers in order to help find out what providers need. Therefore, Frontdesk has a role in achieving provider satisfaction through employee performance in accordance with Service Operational Standards. This research aims to analyze the role of the Frontdesk of the LPSE Section of the Goods and Services Procurement Bureau of East Java Province to achieve Provider Satisfaction. The research method used is descriptive qualitative with a literature study approach, interviews, observation and documentation. The results of this research show that the Frontdesk of the LPSE Section of the East Java Province Goods and Services Procurement Bureau has a role in achieving provider satisfaction by providing good service and employees working in accordance with service operational standards.